Dakwah sebagai Proses Transformasi Sosial Perspektif KH. Hasyim Asy'ari - Ahmad Fahri; Faiz Fikri Al Fahmi; Fithriya Hartin Dzulqa'idah; Farhan Ghalib; Najwa Novia Handayani; Dewi Shafira (ISME : Journal of Islamic Studies and Multidisciplinary Research, 2025)
KH. Hasyim Asy’ari is the founder of Nahdlatul Ulama and an Islamic scholar who emphasized the importance of integrating creed (aqidah), knowledge, ethics, and social responsibility in da’wah. This research is motivated by the phenomenon of a shift in the meaning of da’wah, which has become increasingly ceremonial and less focused on social transformation. Given these values and conditions, his thoughts remain highly relevant to contemporary Islamic preaching. This study employs a qualitative approach with library research as the method of data collection, drawing upon KH. Hasyim Asy’ari’s works and related literature discussing his views on transformative da’wah. The aim of this study is to examine his da’wah ideas as a form of social transformation in the context of Islamic society in Indonesia. The conclusion of the study is that KH. Hasyim Asy’ari’s concept of da’wah can serve as a methodological foundation for developing a holistic, responsive, and principled da’wah model rooted in the values of Ahlus Sunnah wal Jama’ah, which stands as a central pillar of Islam in Indonesian society.